Need Analysis and Development of Webtoon-based Online Comics for Public Middle Schools: A Preliminary Study - Zaitun Zaitun; Kasmiati Kasmiati; Nurhayati Zein; Raja Rahima MRA.; Musa Thahir (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
This research investigates the understanding of religious moderation among teachers and students in the context of Islamic Religious Education. The results of this research are based on data analysis from a survey conducted in junior high schools. The research results show that the majority of teachers and students have a positive attitude towards religious moderation, including acceptance of state ideology, respect for ideological diversity, and an attitude that rejects violence on the basis of religion. Apart from that, they also show tolerance towards different local cultures. These findings have important implications in the educational context, especially in efforts to increase understanding of religious moderation among the younger generation.